Kyoto gardens - Nakane, Kinsaku (Hoikusha, 1979)
The importance of Kyoto's role as the capital city and chief center of culture in Japan for over a thousand years is clearly revealed by the many noteable gardens, which range in date from the Heian period to the first years of the twentieth century, that are preserved at various locations in and around the city today.